A quality improvement project to decrease utilization of multilumen peripherally inserted central catheters. (25th February 2021) - Kleinman Sween, Jennifer; Lowrie, Angela; Kirmse, Jane M.; Laughlin, Rena Kane; Wodziak, Brooke; Sampathkumar, Priya
Abstract: We performed a quality improvement project to decrease utilization of multilumen peripherally inserted central catheters (PICCs) in favor of single-lumen PICCs and midline catheters. Through optimization of electronic orders, education and decision support, we decreased utilization of multilumen PICCs, changed provider ordering patterns, and showed a downward trend in CLABSIs.